St. Christoph am Arlberg Die Geschichte von Hospiz und Taverne, Kapelle und Bruderschaft, von Brücken, Wegen und Straßen, Säumern, Wirten und anderen Menschen an einem Alpenpass (Ende des 14. bis Mitte des 17. Jahrhunderts) - Büchner, Robert (2005)
Based on the evaluation of extensive sources the book presents the history of an Alpine pass as a living space for many people. Whether it was merchants, grocers, pedlars, wagoners and sumplers, peasants, shepherds, wardens, hosts, miners, soldiers, messengers, pilgrims, beggars, gypsies or vagrants, they all had to get accustomed to the high mountains and to cope with rain, fog, storm, snow, ice, avalanches, mudflows and rockfalls. The rigour of the weather required frequent repairs of the paths, roads and bridges. Since the end of the fifteenth century, wagoners could no longer pass the Arlberg, only samplers. Among other articles of trade they transported food, especially "Schmalz" (boiled butter) to the towns of Innsbruck and Hall on packhorses and in return brought back salt to Vorarlberg and Switzerland. On the summit of the Arlberg a "Hospiz" (mountain hostel) has provided shelter, supplies of food and help for travellers since 1386. Contrary to the generally held opinion, research showed that there was no fraternity of St. Christoph on the Arlberg in medieval times. At first the "Hospiz" was maintained by donations only, mostly procured by collectors in Austria, Germany and Switzerland, but was turned into a tavern as early as ca. 1420. 17 tavern keepers at St. Christoph, mentioned between ca. 1500 and 1659, has been described in the book, some of them in close detail.